Upaya Pencegahan Stunting Sejak Dini Di Praktek Mandiri Bidan Sary Rahayu, S.ST Tahun 2024 - Khairulisni Saniati (Institut Nalanda, 2024)
Stunting is a condition of failure to thrive in babies under five years old (toddlers) caused by chronic malnutrition and exposure to repeated infections over a long period of time, especially in the first 1000 days of life (HPK), namely from the womb until the child is two years old. Signs that a child is stunted are that the child's height is shorter or stunted than the standard for children of their age. The condition of stunting only appears after the baby is 2 years old as indicated by a standard deviation (SD) z unit (z-score) value of height for age (TB/U) <-2 SD for short toddlers and <-3 SD for very short toddlers according to World Health Organization (WHO) standards (Indonesian Ministry of Health, 2016).